2023
DOI: 10.3390/biomedicines11123343
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A Gene Mutations: Implications for Hereditary Cancer Syndromes

Anastasiia Danishevich,
Airat Bilyalov,
Sergey Nikolaev
et al.

Abstract: Malignant neoplasms, including pancreatic cancer and melanoma, are major global health challenges. This study investigates melanoma pancreatic syndrome, a rare hereditary tumor syndrome associated with CDKN2A gene mutations. CDKN2A mutations contribute to a lifetime risk of melanoma ranging from 28% to 67%. This study reports the clinical features of six individuals with CDKN2A mutations and identifies recurrent alterations such as c.307_308del, c.159G>C and c.71G>C. It highlights the need for CDKN2A mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In 1994, it was found that inherited genetic mutations could deactivate CDKN2A. This finding was a significant advancement in melanoma genetics, identifying CDKN2A as a primary predisposing gene responsible for 10–40% of hereditary melanoma cases [ 27 ]. Disabling CDKN2A enhances the susceptibility to CDK4/6 inhibitors in certain types of cancer cells, such as melanoma.…”
Section: Melanoma Mutations Of Importance (Summarized In Ta...mentioning
confidence: 99%
“…In 1994, it was found that inherited genetic mutations could deactivate CDKN2A. This finding was a significant advancement in melanoma genetics, identifying CDKN2A as a primary predisposing gene responsible for 10–40% of hereditary melanoma cases [ 27 ]. Disabling CDKN2A enhances the susceptibility to CDK4/6 inhibitors in certain types of cancer cells, such as melanoma.…”
Section: Melanoma Mutations Of Importance (Summarized In Ta...mentioning
confidence: 99%